Perempuan dan Lingkungan : Keterlibatan Perempuan Kamboja dalam Program UN- REDD+ Periode 2008-2019 - Lila Afifa Astin (Universitas Airlangga, 2020)
Cambodia is a country with the third-highest rate of deforestation in theworld. In 2016, for example, Cambodia lost 28,612 square kilometersof green forest and 87,424 square kilometers of permanent forest. Thislarge number of deforestations, in the end, raises national problems, bothpolitical, economic, and social. The shifting role of women, especiallyCambodian women who depend on forest resources, is one of the effectsof the environmental degradation that happened in the country. If womencould always depend on nature in the past, now women have to worktwice as much to meet their needs. Efforts to reduce global environmentalproblems in the United Nations Reducing Emissions for Deforestationand Degradation (UN-REDD+) program in 2008 have become a breathof fresh air for Cambodia’s environmental problems. In this article, theauthor describes the role of Cambodian women’s involvement in the UNREDD+ program in 2008-2019 to address environmental and climatechange that occurred in the country.